1996
DOI: 10.1103/physrevc.53.2638
|View full text |Cite
|
Sign up to set email alerts
|

Integral equation calculations for the photodisintegration processHe4(γ, n)

Abstract: Results obtained by solving Alt-Grassberger-Sandhas ͑AGS͒-type integral equations for the photodisintegration of 4 He, employing the Malfliet-Tjon potential, are compared with the latest experimental data. Good agreement between theory and experiment is found in electric dipole approximation for the total cross section, but the differential cross sections differ at higher energies. This discrepancy is reduced, but not fully removed by taking into account the electric quadrupole contributions. In order to get s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
38
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 35 publications
7
38
1
Order By: Relevance
“…In Refs. [6,7,8] it has been shown that such models lead to pronounced peak cross sections, in rather good agreement with the experimental data of [1] and much different from what was calculated earlier [9].…”
supporting
confidence: 72%
“…In Refs. [6,7,8] it has been shown that such models lead to pronounced peak cross sections, in rather good agreement with the experimental data of [1] and much different from what was calculated earlier [9].…”
supporting
confidence: 72%
“…Of particular controversy is the height of the cross section at the peak, alternatively found to be either pronounced or suppressed with differences up to a factor of 2 between different experimental data. With the exception of [17], early evaluations of the 4 He photo-disintegration [18,19,14] showed better agreement with the high-peaked experiments, and, ultimately, with those of Ref. [16].…”
mentioning
confidence: 50%
“…For the AV18/UIX potential model we have realized that the sum of the CSs σ n, 3 He + σ p, 3 H of the reactions 4 He(γ, p) 3 H and 4 He(γ, n) 3 He does not reproduce the inclusive CS. This discrepancy is the result of neglecting the 3NF in the source term of the exclusive LIT equation (6). We intend to explore this point including also the 3NF in the source term.…”
Section: Discussionmentioning
confidence: 99%
“…In the low-energy regime, the total cross section of the two-body breakup reactions is well-described by the unretarded dipole approximation (UDA) [6,7]. Therefore meson-exchange currents can be included implicitly using Siegert's theorem.…”
Section: Introductionmentioning
confidence: 99%